A nonlocal stochastic Cahn–Hilliard equation. (July 2016) - Cornalba, Federico
Abstract: We consider a stochastic extension of the nonlocal convective Cahn–Hilliard equation containing an additive Wiener process noise. We first introduce a suitable analytical setting and make some mathematical and physical assumptions. We then establish, in a variational context, the existence of a weak statistical solution for this problem. Finally we prove existence and uniqueness of a strong solution .